2006
DOI: 10.1158/1078-0432.ccr-05-2747
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Tumor Redox Status by Magnetic Resonance Imaging Using Nitroxides as Redox-Sensitive Contrast Agents

Abstract: Purpose: There is considerable research directed toward the identification and development of functional contrast agents for medical imaging that superimpose tissue biochemical/molecular information with anatomical structures. Nitroxide radicals were identified as in vivo radioprotectors. Being paramagnetic, they can provide image contrast in magnetic resonance imaging (MRI) and electron paramagnetic resonance imaging (EPRI). The present study sought to determine the efficacy of nitroxide radioprotectors as fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 38 publications
4
161
0
Order By: Relevance
“…Studies showed that nitroxides provide significant contrast enhancement in phantom objects and that the rate of decrease in intensity measured by T1-weighted MRI scans can be used as an indicator of metabolism of nitroxides as a function of time [5]. In vivo experiments using the nitroxide 3CP were carried out in tumor bearing mice to examine the differences in nitroxide metabolism in tumor and normal tissue [6].…”
Section: Functional Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that nitroxides provide significant contrast enhancement in phantom objects and that the rate of decrease in intensity measured by T1-weighted MRI scans can be used as an indicator of metabolism of nitroxides as a function of time [5]. In vivo experiments using the nitroxide 3CP were carried out in tumor bearing mice to examine the differences in nitroxide metabolism in tumor and normal tissue [6].…”
Section: Functional Imagingmentioning
confidence: 99%
“…This ability to participate in redox reactions enables nitroxides to protect against oxidative damage in several models ranging from cell systems to isolated organs to whole animal models including humans [4]. More recently, they have been recognized as redox-sensitive paramagnetic contrast agents in Magnetic Resonance Imaging (MRI) [5,6]. In this review the chemical basis for the protective effects of nitroxides as well as the cellular and in vivo studies will be summarized.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this surrogate decay rate calculated based on decreasing T 1 -weighted MRI contrast can be used as a fallback position was discussed to ensure in vivo redox mapping based on T 1 -weighted MRI, which was reported elsewhere. [27][28][29] In addition, the suitability of conventional nitroxyl paramagnetic contrast agents, such as 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (TEMPOL) and 3-carbamoyl-2,2,5,5-tetramethylpyrrolidine-N-oxyl (CmP), as redox probes for MR redox imaging based on T 1 -contrast was also discussed. ; 4-9-1 Anagawa, Inage-ku, Chiba, Chiba 263-8555, Japan: and b Radiation Biology Branch, Center for Cancer Research, National Cancer Institute, NIH; Bethesda, MD 20892-1002, U.S.A.…”
Section: )mentioning
confidence: 99%
“…Recently, high-power magnet MRI instrumentation, such as 4.7 T, with a T 1 -weighted spoiled gradient echo (SPGR) pulse sequence has enabled us to take a fresh look at the feasibility of employing nitroxyl radicals as MRI contrast agents. [27][28][29] The redox status of the tumor and normal tissue can be reflected in the time course of T 1 contrast after the injection of a paramagnetic nitroxyl contrast agent to an experimental animal.Gradient echo (GE)-based T 1 -weighted contrast imaging is fast and is suitable for dynamic imaging, although T 1 -weighted MRI contrast can not be utilized to quantify the amount of contrast agent directly. The pseudo decay rate calculated based on decreasing T 1 -weighted MRI contrast can show a similar value to the decay rate obtained by EPR measurement when an identical phantom sample is measured by both methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation